CULTURE SHOCK AS A SOCIAL ISSUE - Egamberdiyeva Irodaxon; Abdulhakimova Mohlaroyim; Maxkamova Diyora (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. This article explains the meaning of culture shock , its causes and the solutions for culture shock in today's society. In this article you can take information about culture shock and become aware of some conflicts that cause because of culture shock.